Human Papillomavirus Epidemiology and Prevention: Is There Still a Gender Gap? - Giovanna Milano; Giovanni Guarducci; Nicola Nante; Emanuele Montomoli; Ilaria Manini (Vaccines, 2023)
Background and aim: Human papillomavirus (HPV) is sexually transmitted, one of the three most common sexually transmitted infections (STIs) in both males and females, and the most common viral STI. A crucial public health strategy to protect people against HPV is vaccination, which has shown its effectiveness in preventing HPV-related diseases. Presently, three types of vaccines are available (bivalent, quadrivalent, and nonvalent), and they all target the two most oncogenic virus genotypes (HPV 16 and 18). In recent years, the need to implement vaccination programmes that include all genders has been discussed in order to achieve herd immunity against HPV. To date, only a few countries have included young males in their vaccination programmes. Thus, our objective with this review is to provide an overview of the epidemiology of HPV and HPV prevention strategies and report the latest findings from the scientific literature.